2022
DOI: 10.1109/access.2022.3200834
|View full text |Cite
|
Sign up to set email alerts
|

On Performance of STAR-RIS-Enabled Multiple Two-Way Full-Duplex D2D Communication Systems

Abstract: This paper investigates performance of simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS)-enabled multiple two-way full-duplex device-to-device (D2D) communication systems over Rayleigh fading channels under optimal and uncertain phase shift alignments. We derive closed-form expressions for outage probability (OP), sum throughput, ergodic capacity (EC) and energy efficiency. To gain insights, we quantify and reveal some useful guidelines for the performance behavior of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…1) Angular-Domain Reciprocity: Considering that the channels between a source and the TRX arrays have spatial correlations owing to the common scattering environment, the angular-domain reciprocity of the TRX channels holds due to the far-field planar wavefront assumption 2 . That is, when the distance between the TRX arrays and the source is far enough, the planar wavefront is assumed to make the TRX arrays' direction angles have a constant phase difference.…”
Section: B Channel Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…1) Angular-Domain Reciprocity: Considering that the channels between a source and the TRX arrays have spatial correlations owing to the common scattering environment, the angular-domain reciprocity of the TRX channels holds due to the far-field planar wavefront assumption 2 . That is, when the distance between the TRX arrays and the source is far enough, the planar wavefront is assumed to make the TRX arrays' direction angles have a constant phase difference.…”
Section: B Channel Modelmentioning
confidence: 99%
“…These studies considered the HD system. The research most relevant to our work, i.e., RIS-aided FD, was documented in [2], [29]- [32]. Through studying the outage probability, the authors in [29] demonstrated the superiority of the RIS-aided two-way systems compared to the oneway counterpart.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations